Efektifitas Konseling Kelompok dalam Mengurangi Kecemasan Sosial dan Akademik Siswa: A Systematic Literature Review - Hashi, Renanda Asfarina (Universitas PGRI Semarang, 2025)
Social and academic anxiety are two crucial issues that often affect students' well-being in the educational environment. Group counseling has been the subject of intensive attention in an effort to reduce the negative impact of anxiety. This article presents a systematic literature review to explore the effectiveness of group counseling in overcoming social and academic anxiety in students with various approaches and techniques. This research aims to determine and test the effectiveness of group counseling approaches and techniques in reducing social and academic anxiety in students. The results of this research reveal various group counseling approaches and techniques, including Cognitive Behavioral Therapy, Behavioral Rehearsal Approach, Cognitive Restructuring, Systematic Desensitization, Thought-Stopping, Stress Inoculation Training, Self-Management, Rational Emotive Behavioral Therapy, Self-talk, and Analysis Transactional. The 20 articles we have collected prove that the various approaches and techniques above are effective in reducing the level of social and academic anxiety in students.